THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) IN TEACHING ENGLISH AS FOREIGN LANGUAGE IN JUNIOR HIGH SCHOOL IN SOUTH SULAWESI INDONESIA - Zahra, Andi; Baa, Sultan (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The objectives of this research were to discover: (1) the teachers’ perceptions on the implementation of PBL in teaching English as foreign language; (2) the classroom implementation of PBL in teaching English as foreign language; and (3) the students’ perceptions on the impact of PBL in English learning in junior high school in South Sulawesi. The study applied mixed method research design. This research was conducted at MTs Darul Istiqamah Makassar. The subjects of the research consisted of English teacher and students from eighth and ninth grade. Observation, interview, and questionnaire were used to collect data. Teacher interview was used to collect data on the teacher’s perception on the implementation of PBL, while classroom observation was used to discover the PBL practice in the classroom. In addition, questionnaire was also used to assess the students’ perceptions on the impact of PBL in learning English. The results of this research revealed that: (1) the perceptions of two teachers about the implementation of PBL in teaching English as foreign language are varied from their reasons for choosing problem-based learning; their challenges in implementing PBL in classroom; and the benefits of problem-based learning for students; (2) the teacher had implemented the syntaxes of PBL such as orientation to the problem, organizing the learner, guiding the investigation, developing students’ work and evaluating PBL process. However, the classroom activities carried out was not really suitable with the characteristics of PBL; and (3) the students’ perceptions on the impact of PBL in learning process was largely agreed in terms of the benefit of PBL for them. Detailed findings will be presented and their implications discussed.